Rational design and synthesis of 6-aryl-6H-benzo[c]chromenes as non-steroidal progesterone receptor antagonists for use against cancers. (15th February 2021) - Qin, Jing; Qu, Sifeng; Zhu, Kongkai; Cheng, Yahong; Pan, Ge; Jing, Weiqiang; Liu, Xigong; Sun, Xia; Liu, Lei
Graphical abstract: Highlights: The novel non-steroidal PR antagonists were designed and synthesized. Structural features related to anti-cancer activity were identified by SAR analysis. Derivatives 32 and 34 displayed potent anti-cancer activity against MCF-7 cells. Derivatives 32 and 34 induced cell apoptosis through activation of p53 pathway. Abstract: Progesterone receptor (PR) antagonists have been found to be effective for treating certain human cancers. However, the steroidal structure of PR antagonists could bind to other hormone receptors, thus leading to serious side effects. On the other hand, non-steroidal PR antagonists have rarely been evaluated for their anti-cancer efficacy. Therefore, identifying novel non-steroidal PR antagonists possessing potent anti-cancer efficacy would be an attractive project to pursue. In this study, we presented a new metal-free oxidative CH arylation method to rapidly synthesize a series of 6-aryl-6 H -benzo[ c ]chromene derivatives. Multiple cancer cell lines were used for their anti-cancer activity screening. An extensive analysis of structure–activity relationships (SAR) of the derivatives revealed that compounds 32 and 34 markedly inhibited the proliferation of MCF-7 cells with IC50 values of 6.32 ± 0.52 μM and 5.71 ± 0.49 μM, respectively. Further investigation indicated that derivatives 32 and 34 could elevate the expression of p21 and decrease the expressions of CDK4 and cyclin D1, leading to cell cycle arrest at G0/G1 phase. In addition, derivatives 32 and 34 could induce apoptosis of MCF-7 cells in both dose- and time-dependent manners by activation of p53 pathway, i.e., activation of Cleaved Caspase-3, p53 and P-p53 as well as elevation of the Bax/Bcl-2 ratio. Docking of derivatives 32 and 34 into a PR homology model exhibited potent PR antagonistic activity indicating the 6-aryl-6 H -benzo[ c ]chromene derivatives are promising PR antagonists. We envisioned that derivatives 32 and 34 might be potential anti-cancer drug candidates as novel therapeutic treatment for breast cancer.